Description of pharmaceutical interventions and clinical impacts of a new electronic tool used to identify and manage medication of vulnerable hospitalized elderly patients - Joëlle Flamand-Villeneuve; Julie Boisvert; Pascale Blais-Lecours; Cassandra Denis; Catherine Denis; Julie Méthot (Canadian Pharmacists Journal / Revue des Pharmaciens du Canada, 2026)
Abstract Background: Older adults are at high risk of medication-related problems due to polypharmacy and potentially inappropriate medications (PIMs) use. A computerized tool was developed at Institut Universitaire de Cardiologie et de Pneumologie de Québec-Université Laval (IUCPQ-UL) to identify older patients who may benefit from pharmacist-led interventions. Methods: This prospective longitudinal descriptive study described the number and types of geriatric pharmacological problems detected by the electronic tool among patients aged 75 years and older admitted to targeted clinical units. Results: A total of 67 patients were included in the data analysis. Ninety-nine potential pharmacological problems were detected, with an average of 1.5 ± 0.8 problems per patient. The 2 most frequently identified potential problems were “osteoporosis and 15 home medications” (32%) and "1 or more PIMs" (21%). A total of 139 interventions were carried out, including 107 directly related to the identified potential pharmacological problems. An average of 40 minutes was required to perform 2 interventions per patient. Complex cases included patients with more geriatric syndromes and required more time. These tended to result in a greater number of pharmacological interventions. Discussion: The use of the tool led to at least 1 intervention in the majority of cases, with a reasonable amount of time invested. Most interventions did not require the expertise of a pharmacist specialized in geriatrics. Conclusion: The electronic tool developed at IUCPQ-UL successfully identifies older patients at risk of medication-related problems for whom interventions are possible. It can be easily used by non-geriatric clinical pharmacists, making it broadly applicable across hospital settings.